Respuesta :

Answer:0

Step-by-step explanation:

Simplifying

2x + -1x + 7 = x + 3 + 4

Reorder the terms:

7 + 2x + -1x = x + 3 + 4

Combine like terms: 2x + -1x = 1x

7 + 1x = x + 3 + 4

Reorder the terms:

7 + 1x = 3 + 4 + x

Combine like terms: 3 + 4 = 7

7 + 1x = 7 + x

Add '-7' to each side of the equation.

7 + -7 + 1x = 7 + -7 + x

Combine like terms: 7 + -7 = 0

0 + 1x = 7 + -7 + x

1x = 7 + -7 + x

Combine like terms: 7 + -7 = 0

1x = 0 + x

1x = x

Solving

1x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.

1x + -1x = x + -1x

Combine like terms: 1x + -1x = 0

0 = x + -1x

Combine like terms: x + -1x = 0

0 = 0

Simplifying

0 = 0

The solution to this equation could not be determined.